Teacher Strategies in Preventing Verbal and Physical Violence at the Educational Unit Level - Yati; Ojat Darojat; Fitra Jaya; Sucipto; Romi Siswanto; Kadarisman (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
Violence in educational units is a crucial issue that negatively impacts the psychological and academic development of students. Teachers play a strategic role in preventing and addressing violence within the school environment. This study aims to identify strategies that can be implemented by teachers to prevent violence in educational units. The research employs a qualitative approach with data collected through interviews, observations, and literature reviews. This study highlights the importance of enhancing teachers' capacities through more comprehensive training so that they can become agents of change in creating a safe and inclusive educational environment. The findings indicate that violence prevention strategies can be implemented through three main approaches, namely: Preventive Approach: Involves the implementation of character education, the creation of a positive school culture, and effective communication among teachers, students, and parents. Intervention Approach: Involves the early detection of potential violence, the engagement of school counselors, and the use of technology in monitoring student behavior. Rehabilitative Approach: Involves providing psychosocial support for both victims and perpetrators, as well as recovery programs based on inclusiveness. With active teacher involvement in preventing violence, it is expected that the incidence of violence will decrease, allowing students to develop optimally within a positive learning environment. This study recommends strengthening teachers' capacities in pedagogical, psychological, and social aspects so that they can serve as effective agents of change in creating a safe and comfortable educational environment.